Entangled lives: drug assemblages in Afghanistan's Badakhshan. Issue 11 (2nd November 2022) - Goodhand, Jonathan; Pain, Adam
Abstract: This article, focussing on Badakhshan province in north-east Afghanistan, explores the lifeworld of drugs and their entangled connections with people, places and things. It follows the journeys of drugs from the farmers' fields, through their various stages of transportation, storage and transformation, until they arrive at the border with Tajikistan. The paper draws upon the notion of a 'drugs assemblage' – the interweaving of plants, institutions, actors, processes and resources through which drug journeys are managed and facilitated. Drugs are embedded in a web of social relations that connect farmers, labourers, shopkeepers, smugglers, brokers and border guards. Opium is central to the production of a Braudelian geography, fragmented yet connected, of trading routes, enclaves, choke points and border crossings. Drugs have played a role in transforming the 'disturbed' landscape of this remote borderland region, into a centre of innovation and improvisation, in which alienation and precarity co-exist alongside accumulation and the pursuit of 'freedom'.